Uterine fibroids of gigantic size: a clinical case - Marina V. Koval; Anna M. Bogdanova; Georgy P. Svetlakov; Irina Yu. Kovaleva; Vilena I. Chashchina (Гинекология)
Uterine fibroid (UF) is the most common benign tumor in the structure of gynecological diseases of the female reproductive system, accounting for 45–70% of the total cases. Special attention should be paid to the rare cases with gigantic UFs. The management approach to patients with gigantic UFs is determined by the age of the patient, her desire to bear a pregnancy and realize reproductive function, as well as the presence of comorbidities. Therefore, an individualized approach is essential. The paper describes a clinical case of a patient with a gigantic UF that grew due to the lack of proper medical care for a long time. The patient underwent panhysterectomy, resection of the greater omentum, and ligation of the internal iliac arteries. This case is a clear example of the forced extension of the surgical procedure due to the tumor size, which is associated with an increased risk of surgical complications